Environmental Dynamics and Risk: Bibliometric Insights into Soil Heavy Metal Accumulation Under Environmental Stressors - Jiaxiang Wang; Yueyao Li; Yimin Zhou; Jibai Long; Zhuoqing Li; Cheng Qiu; Qinghai Liu; Ming Lei (BioResources)
Under environmental stress, the migration and accumulation of heavy metals in soil profoundly affect ecosystem dynamics and environmental risks. This study applied CiteSpace bibliometric methods to visually analyze 1,768 publications from 2000 to 2024, based on the Web of Science Core Collection. The analysis included publication trends, keyword frequencies, international collaboration, core authors, and institutions. Results show a shift in focus from pollution identification and mechanisms to health risk assessment and material-based remediation. Notably, increasing attention has been given to lignocellulose-derived amendments such as humic acid and biochar for their potential in stabilizing soils under compound environmental stressors. Leading institutions such as the Chinese Academy of Sciences and U.S. research bodies have played prominent roles, while high-impact journals, including the Journal of Biogeography, reflect strong academic output. Keyword clustering and burst analysis highlight emerging cores like “speciation,” “health risk,” and “biochar,” showing a phase-based evolution of research themes. The field’s short citation half-life, frequent keyword bursts, and multidisciplinary integration confirm its status as a research frontier. This study provides a comprehensive knowledge map and valuable insight into the dynamic behavior of soil heavy metals under environmental stress.